Investigating and modelling sediment transportation by means of natural radionuclides as tracers in East London Harbour, South Africa - Botlholo, Rehab Kgomotso (Stellenbosch : Stellenbosch University, 2025)
Thesis (MMil)--Stellenbosch University, 2025.